PREVALENCE OF HEPATITIS B AND C IN HEALTHY ADULT MALES OF PARAMILITARY PERSONNEL IN PUNJAB - din, Hafeez -ud-; Siddiqui, Tahir Saeed; Lahrasab, Waseem; Sharif, Muhammad Ashraf (Journal of Ayub Medical College Abbottabad, 2012)
Background: Global prevalence of Hepatitis B varies from high (>8%) in Africa, Asia and Western Pacific to low (<2%) in Western Europe, North America and Australia. An estimated 180 million people worldwide including 4 million people in USA are infected with HCV. This cross-sectional observational study was carried out at Department of Pathology, Pakistan Rangers (Punjab) Central Hospital, Lahore from March to June 2010 to determine prevalence of HBV and HCV infection among serving asymptomatic healthy adult males of paramilitary force. Methods: The healthy adult males from province Punjab serving in Pakistan Rangers Punjab without previous history of known positivity for HBV or HCV infection were included in the study. Demographic data including the district of origin were noted. HBsAg and anti-HCV antibodies were tested by rapid immuno-chromatographic method while positive tests were reconfirmed by enzyme immuno-assay (EIA). Results: Out of total 15,793 adults screened for Hepatitis B & C viral infections, 14,027 adults belonged to the province of Punjab. There were 396 (2.82%) adults who were found positive for HBsAg and 511 (3.64%) positive for anti-HCV on screening. Retesting of the positive tests by EIA showed 396 (2.82%) positive for HBsAg, and 440 (3.13%) for anti-HCV respectively. Specificity of immune chromatographic method for HBsAg and anti-HCV calculated taking EIA as gold standard was 100% for HBsAg and 99.5% for anti-HCV while positive predictive value of the immuno-chromatographic methods was 100% for HBsAg and 86.1% for anti-HCV. Highest of prevalence of HBsAg was seen in Rahimyar Khan (7.58%) while high prevalence of anti-HCV was seen in Chiniot (8.9%), Faisalabad (7.2%), Vehari (7.03%), Muzaffargarh (5.95%) and Sheikhupura (5.83%). Conclusion: Overall prevalence of HBsAg and anti-HCV is on the decline. The isolated pockets of very high prevalence of HCV infection in the districts of Chiniot, Faisalabad, Vehari, Sheikhupura, Rahimyar Khan, Muzaffargarh, and Okara pose a community health problem with a dire need to adopt strict preventive measures in the medical and social practices with effective public awareness campaigns. Keywords: HBsAg, Anti-HCV, Hepatitis